Process Control - A Practical Approach (2nd Edition) - King, Myke (John Wiley & Sons, 2016)
This expanded new edition is specifically designed to meet the needs of the process industry, and closes the gap between theory and practice. Back-to-basics approach, with a focus on techniques that have an immediate practical application, and heavy maths relegated to the end of the book; Written by an experienced practitioner, highly regarded by major corporations, with 25 years of teaching industry courses; Supports the increasing expectations for Universities to teach more practical process control.